THE KINETIC OF CYCLIZATION-ACETYLATION (R)-(+)-CITRONELLAL WITH ANHYDRIDE ACETIC ACID WHICH CATALYZED OF Zn2+-NATURAL ZEOLITE - Edy Cahyono; M. Muchalal; Triyono Triyono; Harno Dwi Pranowo (Jurnal Zeolit Indonesia, 2009)
Reaction kinetic of acetylation-cyclization (R)- (+)-citronellal with acetic acid anhydride which catalyzed Zn2+-zeolite (Zn2+-Za) was analyzed by Langmuir- Hinshelwood Models. (R)-(+)-citronellal isolated from lemongrass oil with fractionation distillation reduced pressure and analyzed anantiomer ratio with GC chiral column Î²- DEX 225. Catalyst preparation of Zn2+-Za conducted by acid activation on natural zeolite Malang 100 mesh using 1% HF and 6 M HCl, then soaked on 0,1 M NH4Cl. Calcination was done at 450oC during 1 hour with N2 flow to achieved H-natural zeolite (HZa). Cation exchange H-Za with 0,1 M ZnCl2 conducted to obtain Zn2+-natural zeolit (Zn2+-Za). Reactions of Cyclization-acetylation (R )-(+)- citronellal using a catalyst of Zn2+-Za was done by varying molar ratio of (R )-(+)- citronellal with acetic acid anhydride, namely 0.25, 0.5, 1.0; 1 , 25; 1.5. During the reaction, into system, samples were taken each 1 mL of reaction with duration 10, 20, 30, 60, 120, 180 minutes. Reaction product was extracted with n-hexana. Structure elucidation was done by GC-MS, FTIR spectrophotometer, and 1H-NMR spectrometer. The result showed a greater molar ratio (R)-(+)-citronellal against quantity of acetic acid anhydride acetic, pulegil total was decline. Acetylation-cyclization catalyzed with Zn2+-Za on duration of 30 minutes and 80°C has k of 30.964 to 47.619 mmol (minute.gram catalyst)-1 and KSIT/KAA of 7.09.